Tap, click, read : - Guernsey, Lisa (Jossey-Bass, A Wiley Imprint, 2015)
With young children gaining access to a dizzying array of games, videos and other digital media, will they ever learn to read? The answer is yes – if we ensure that the media at children’s fingertips is harnessed to promote the skills and knowledge that enable reading, instead of undermining them. 'Tap, Click, Read' helps educators and parents become more successful at supporting young children’s early literacy skills in the "digital wild west."